REALIZATION OF EXPERIENTIAL FUNCTION OF NATIONAL ANTHEM OF INDONESIA - Sri Heriyani Nasution; Amrin Saragih; Rahmad Husein (LINGUISTIK TERAPAN, 2018)
This qualitative study is aimed to find the Realization of Experiential Fuction of National Anthem of Indonesia. It was conducted by applying documentary study. The data analysis for this research was the text of National Anthem of Indonesia. The data were collected by applying a documentary technique. The document was read and analyzed to find out the Experiential Function. The data were analyzed by some procedures: data condensation, data display and drawing conclusion. Every elements of experintial function in the song or National Anthem represents the purpose of the song because the experiential function functions to represent the experience. The researcher also found there are so many ellipsis word in the song. Where that element can be found or detected from the context. Ellipsis means what is something left of linguistic elements. The ellipsis use because song is the simple language.Keywords: Experiential Function, National Anthem, Discourse, Text and Context